Capturing aerosol droplets with fibers. Issue 35 (2nd August 2019) - Labbé, R.; Duprat, C.
Abstract : Capturing droplets from a stream with a fibrous material is a well-known process, from coalescence filters to fog harvesting. The collection efficiency strongly depends on the drop distribution on the fibers, thus on their wetting properties. Abstract : Capturing droplets from a stream with a fibrous material is a well-known and well-used process, from coalescence filters to fog harvesting. In this paper, we report experimental measurements of collection efficiency with a model system consisting in an array of vertical nylon fibers. In particular, we report precise measurements over a large range of parameters, and identify the key role played by the drop distribution on the overall collection efficiency. Due to a growth and coalescence process, this drop distribution evolves toward a regular pattern of uniformly distributed drops, and a balance between capillarity and gravity sets an average drop size. Accounting for these effects in a simple inertial impaction model allows predictive and quantitative comparisons with experiments. Drop growth can be suppressed by forming long continuous liquid columns between close fibers; incoming droplets immediately coalesce with these wet columns, and the capture efficiency is increased. In addition, we extend our model to take into account the interactions between fibers.